Detailed analysis of particulate emissions of a multi-cylinder dual-mode dual-fuel engine operating with diesel and gasoline. (15th December 2022) - García, Antonio; Monsalve-Serrano, Javier; Villalta, David; Fogué-Robles, Álvaro
Highlights: Experimental measurement of particulate numbering on multi cylinder engine. Estimation of particulate mass from dual-fuel dual-mode engine. Evaluation of the impact of a diesel oxidation catalyst on particulate emissions. Analysis of the particle size distribution with different combustion modes. Technological comparison with bibliographic data on other combustion concepts. Abstract: Internal combustion engines are still within the future of highway transport. Low-temperature combustion modes are prone to substitute conventional diesel combustion engines, seeking better performance and improved emissions control. The dual-mode dual-fuel combustion approach has been confirmed as a feasible combustion mode for achieving ultra-low NOx and soot emissions simultaneously. The aim of this work is to experimentally measure the particle emissions of the dual-mode dual-fuel concept while maintaining good thermal efficiency and EURO VI engine-out NOx levels. A detailed analysis of the most relevant characteristics of the particle size distribution is carried out to depict the requirements of a potential filtering system considering the effects of an upstream diesel oxidation catalyst. The results show that total particle numbering is within the typical values of the current most popular technologies: around 2·10 13 #/kWh for RCCI and around 10 14 #/kWh for DMDF. RCCI combustion tends to produce more particles sized below 35 nm in diameter, while DMDF shows a clear dominance of sizes above 40 nm. In terms of total particulate matter, RCCI results in total mass concentrations around 4 mg/kWh thanks to the highly premixed combustion, but diffusive combustion mode results in total mass emissions over 50 mg/kWh.